Gac aril and gum xanthan supplementation in wheat macaroni pasta production [pdf] - Nguyễn Minh Thủy; Nguyen Thi Tieu Phung; Tran Ngoc Giau; Vo Quoc Tien; Ngô Văn Tài; Võ Quang Minh (Acta Scientiarum Polonorum Technologia Alimentaria, 2023)
Background.Macaroni is a common side dish or main dish that is served with sauces.Traditional macaroni is typically made using flour, water and eggs and is typically yellow in color.It has a high amount of starch and is deficient in fiber, minerals, vitamins and bioactive components.Material and methods.The effects of Gac aril (3, 5, 7 and 9%) and xanthan gum (1, 1.5 and 2%) on the quality characteristics of macaroni were investigated.Macaroni was evaluated for cooking quality (cooking loss, volume increase, rehydration ratio), colour, chemical (β-carotene and lycopene) and structure/microstructure to assess the impact of experimental factors.Results.The proximate composition of Gac aril was analysed and showed that Gac aril added to macaroni recipes is a food ingredient capable of enhancing bioactive compounds (β-carotene and lycopene).Studies on the combined effects of the addition of Gac aril and xanthan gum have shown that macaroni with 7% gac and 1.5% xanthan gum used resulted in a beautifully colored macaroni product (before and after cooking), good structure, high β-carotene and lycopene content (15.26 μg/g and 61.26 μg/g, respectively).The cooking quality of the macaroni was thoroughly analyzed.The rehydration rate and volume both increased with the addition of Gac aril and the xanthan gum content increased.However, the cooking loss was shown to be slightly different.The cooking loss increased as the content of Gac aril supplement was increased, while the added xanthan gum reduced the cooking loss. Conclusion.The effects of macaroni enrichment with gac and the use of xanthan gum on product quality were noted.The physicochemical components, bioactive compounds, firmness, microstructure and cooking quality of the analyzed products emphasized the role of the ingredients used in the results obtained.The microstructure of the product has also been improved and ensures the desired product quality attributes.Further studies are needed in order to be applied at an industrial scale and with high consumer acceptance of this new product.
Keywords: Food composition and properties; Nuts composition and effects; Polysaccharides Composition and Applications